Identification of a Type-Specific Epitope in the ORF2 Protein of Duck Astrovirus Type 1 - Lan, Jingjing (Animals (Basel), 2019)
SIMPLE SUMMARY: Duck astrovirus type 1 (DAstV-1) infection constitutes a cause of viral hepatitis in ducklings and little is known about the B-cell epitope of DAstV-1. In this study, using a monoclonal antibody (mAb) 3D2 against ORF2 protein of DAstV-1, a highly conserved linear B-cell epitope of (454) STTESA(459) in DAstV-1 ORF2 was identified. The mAb 3D2 showed no neutralizing activity to DAstV-1 and had no cross-reactivity with other DAstV serotypes. ABSTRACT: Duck astrovirus type 1 (DAstV-1) infection constitutes a cause of viral hepatitis in ducklings and little is known about the B-cell epitope of DAstV-1. In this study, a monoclonal antibody (mAb) 3D2 against open reading frame 2 (ORF2) protein of DAstV-1 was used to identify the possible epitope in the four serotypes of DAstV. The mAb 3D2 showed no neutralization activity to DAstV-1, and reacted with the conserved linear B-cell epitopes of (454)STTESA(459) in DAstV-1 ORF2 protein. Sequence analysis, dot blot assay, and cross-reactivity test indicated that the epitope peptide was highly conserved in DAstV-1 sequence and mAb 3D2 had no cross-reactivity with other DAstV serotypes. To the best of our knowledge, this is the first report about identification of the specific conserved linear B-cell epitope of DAstV-1, which will facilitate the serologic diagnosis of DAstV-1 infection.